Irrigation Water Chemistry: Impact on Microbial Community Composition and Biogeochemical Leaching under Perennial Ryegrass (Lolium perenne [L]). (30th March 2011) - Holgate, Leon C.; Aitkenhead-Peterson, Jacqueline A.; Gentry, Terry J.
Abstract : Greywater recycling and rain water harvesting for irrigating urban and suburban landscapes may reduce the use of potable water in arid and subtropical climates but affect soil microbial community composition and biogeochemical cycling. Municipal tap water, greywater, and harvested rain water were used to irrigate ( Lolium perenne L.) planted in a constructed soil over a 20 week period. Irrigation with grey water significantly increased the relative abundance of gram-positive biomarkers ANTEISO 15 : 0, ISO 17 : 1G, gram-negative biomarkers 19 : 0 CYCLO c11-12 and bacterial biomarker 18 : 0 (P < .05 ) relative to irrigation with harvested rain water. Significant decreases were observed in the relative abundance of gram-positive biomarker 16 : 0, gram-negative biomarker 16 : 1 ω 7c, both fungi biomarkers (18 : 2 ω 6c and 18 : 1 ω 9c) in soils irrigated with greywater (P < .05 ). Dissolved organic carbon losses from soil were a significant two-to-four times greater from soils irrigated with municipal tap water and greywater relative to soils irrigated with harvested rain water (P < .001 ). This study highlights the effect that municipal tap water and grey water may have on microbial community composition and soil nutrient dynamics under irrigated turf grass.